PENGARUH DISKUSI TAYANGAN FILM PROSOSIAL TERHADAP INTENSI PERILAKU PROSOSIAL ANAK - Arih Merdekasari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2014)
Charged film show prosocial behavior would provide a model for children's prosocial behavior. However, the film can also encourage prosocial to antisocial behavior when the children can not distinguish between acceptable behavior and behavior that is socially unacceptable socially. Discussion of the films have seen prosocial children will provide an understanding of the forms of prosocial behavior and behavior that is not socially acceptable, so that the child will be directed to perform prosocial behavior in everyday life. This study aims to examine the influence of the film show discussion prosocial prosocial behavior toward the child. The hypothesis is there is a discussion of the influence of the film show prosocial intentions to increase children's prosocial behavior. The subjects were taken as the criteria, ie fifth grade elementary school students aged between 10 to 12 years. Further selected 16 children were divided into 2 groups: the experimental group who received treatment and discussion of the film show prosocial control group were only treated prosocial movie viewing. The data collection method using child prosocial behavior intention scale were measured before and after treatment. Results of Wilcoxon signed rank test experimental group (sig = 0.0055) and the control group (sig = 0.416). While the test results of Mann Whitney test post-test score (sig = 0.0075). conclusions, discussion films have prosocial intentions can increase prosocial behavior of children.